COMPREHENSIVE CHARACTERISTICS OF PHYSICAL DEVELOPMENT, SEXUAL DIMORPHISM, VEGETATIVE FUNCTIONS AND HEALTH OF YOUNG MEN OF DIFFERENT ETHNIC AND SAME TERRITORIAL BELONGING - Pulikov, Anatoliy; Petrov, Ivan (Revista Inclusiones, 2020)
In order to reveal the types of body constitution, sexual dimorphism, body mass and density indices, a number of anthropometric indices, vegetative functions and somatic health, we examined, with a complex of gravimetric methods, 348 males (17−21 y.o.), of them 172 Caucasoid and 176 Mongoloid (Khakass) young men in the same climatic-geographical conditions. All young men since birth lived in Khakass Republic, in towns, settlements and villages of Minusinsk Depression and Khakass steppe zone with weak anthropogenic impact, studied at Khakass State University named after N.F. Katanov, national and comprehensive schools. The influence of climatic-geographical and genetic factors was determined. It was stated that the young men of different genotypes mostly have asthenic, dolichomorphic and gynecomorphic body types, with decrease to normosthenic and mesomorphic types and further to pyknic, brachymorphic and andromorphic body types. The dynamic index of the functional status of the neuromuscular system is also at the same (unsatisfactory or poor) level. The peculiar features of Caucasoid young men, related to the phenotype, are: higher gravimetric values, larger number of young men with overweight and obesity, faster growth of lower extremities compared to torso growth, mixed tonus of vegetative regulation with the predominance of parasympathetic part, broader and flatter chest, weaker adaptation to environmental conditions and a resulting moderately weaker health. The genotype preserves the common features characteristic for both races.